2011
DOI: 10.1002/app.34136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the electron beam irradiation on the properties of epoxidized natural rubber (ENR 50) compatibilized linear low‐density polyethylene/soya powder blends

Abstract: Linear low-density polyethylene/soya powder blends were prepared by using an internal mixer at 150 C. The soya powder content ranged from 5 to 40 wt %. Epoxidized natural rubber with 50 mol % epoxidation (ENR 50) was added as a compatibilizer. The blends were irradiated by electron beam (EB) at a constant dose of 30 kGy. The changes in gel fraction, tensile properties, morphological and thermal properties of the samples were investigated. The gel content increased after EB irradiation. However, the increment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…The SSP content was fixed at 5 wt. % based on the optimum properties of our previous research (Sam et al 2012. For compatibilized blends, 0.5% of ENR 50 based on SG was added.…”
Section: Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSP content was fixed at 5 wt. % based on the optimum properties of our previous research (Sam et al 2012. For compatibilized blends, 0.5% of ENR 50 based on SG was added.…”
Section: Mixingmentioning
confidence: 99%
“…The nucleus was then shifted to the interface and the LDPE crystal would grow on the compatible to blends with the compatibilizer. The change to crystallization temperature, T c is minimal but significant (Sam et al 2012).…”
Section: Differential Scanning Calorimeter (Dsc)mentioning
confidence: 99%
“…There are numerous reports on soy‐based plastics with properties inferior to commercial elastomers . Recently, studies have focused on SF as green filler for biocomposites . Among these, there are only three studies focusing on the production and mechanical properties of polyolefin/SF composites in the refereed literature .…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that vulcanized HDPE/ENR treated with phenolic resin exhibited superior mechanical properties and the smallest vulcanized rubber domains . The effect of electron‐beam irradiation on the properties of linear low‐density polyethylene/ENR‐50/SP blends indicated that an increase in the oxygenated product led to enhanced compatibilization in the blend; this, in turn, increased the mechanical properties and thermal stability …”
Section: Other Polymer/enr Blendsmentioning
confidence: 96%